Strengthening teachers’ crisis response: effects of psychological first aid training in elementary schools - Bani Bacan Hacantya Yudanagara; Lantip Muhammad Dewabrata; Chiquita Evita Fatimah; Alifia Khairunisa (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2026)
This study aimed to examine the effectiveness of Psychological First Aid (PFA) training in strengthening elementary school teachers’ crisis response to support students’ psychological well-being. A quasi-experimental one-group pretest–posttest design was conducted. The sample comprised 40 Islamic elementary school teachers in Sidoarjo Regency, recruited using purposive sampling. Data were collected using demographic questionnaires, a PFA knowledge test, and post-training evaluations of perceived effectiveness and affective experiences. Knowledge scores were analyzed using a paired-samples t-test in JAMOVI, and open-ended responses were thematically reviewed. The findings indicated a significant increase in teachers’ knowledge after training (M pre=55,5; M post=73,5; t(39)=4,90; p< 001; Cohen’s d=0,77). Participants also reported enhanced self-confidence and practical skills in delivering PFA to their students, with positive affective experiences emphasizing increased awareness and applicability of PFA. Results demonstrate that PFA training effectively enhances teachers’ preparedness to support students during crises. Future research should employ randomized controlled trials with larger, diverse teacher populations and incorporate follow-up assessments alongside observational measures of teacher practice and student outcomes to comprehensively evaluate PFA training's impact.